Identifying patients with epilepsy at high risk of cardiac death: signs, risk factors and initial management of high risk of cardiac death. Issue 1 (30th March 2021) - Surges, Rainer; Shmuely, Sharon; Dietze, Christoph; Ryvlin, Philippe; Thijs, Roland D.
Abstract: People with epilepsy have a three‐fold increased risk of dying prematurely, and a significant proportion is due to sudden cardiac death or acute myocardial infarctions. The causes of increased cardiovascular morbidity and mortality in epilepsy are manifold and include acute or remote effects of epileptic seizures, the longstanding epilepsy itself or antiseizure treatments. Seizure‐related cardiac arrhythmias are common and comprise bradyarrhythmia and asystole, atrial fibrillation and ventricular tachycardia. The most frequent clinically relevant seizure‐related arrhythmia is ictal asystole that may require implantation of a cardiac pacemaker, whereas seizure‐related ventricular tachycardias are only rarely reported. Takotsubo cardiomyopathy and myocardial infarction are rare complications and predominantly described in association with tonic‐clonic seizures. Epilepsy‐related cardiac complications include a disturbed cardiac autonomic nervous system and acquired dysfunction of the heart (recently defined as 'epileptic heart'), probably contributing to the abnormalities of cardiac repolarisation and elevated risk of sudden cardiac death in people with epilepsy. If successful, the use of antiseizure medication prevents seizure‐related cardiac arrhythmias and remote cardiac complications. However, enzyme‐inducing antiseizure medications have a negative impact on cardiovascular risk factors, which may further be aggravated by weight gain linked to specific antiseizure drugs. Given the severe consequences of cardiac risks, the aim of this educational review is to explain the many facets of cardiac complications and their underlying causes, and to enable the reader to recognize and manage these risks with the goal to mitigate the cardiac risks in people with epilepsy. Features of syncope are explained in detail, as syncope of all origins can be mistaken as epileptic seizures in people with or without epilepsy, and ictal syncope ( i.e . seizure‐induced syncope) can easily be ignored.